Salivary Gland Dysfunction Secondary to Cancer Treatment - Vistoso Monreal, Anette; Polonsky, Gregory; Shiboski, Caroline; Sankar, Vidya; Villa, Alessandro (Frontiers in Oral Health, 2022)
The number of cancer survivors is increasing and so are the oral toxicities from cancer therapy. Most patients receiving treatment for cancer develop some form of oral adverse events including, but not limited to, mucositis, opportunistic infections, dry mouth, and/or osteonecrosis of the jaw. One of the most common complications from head and neck cancer radiation therapy is salivary gland dysfunction (SGD). SGD is an umbrella term that includes the subjective sensation of dry mouth (xerostomia) and hyposalivation (objective reduction of the salivary flow rate). Dry mouth in cancer patients may lead to functional defects (e.g., eating, speaking, and swallowing), increase the risk of dental caries and oral candidiasis, and can have a negative effect on the nutritional and psychological status of the patients. The aim of this mini review was to summarize the current criteria for diagnosis and management of SGD associated with cancer treatment.